Pengaruh Persepsi Pelanggan Tentang Bauran Pemasaran Terhadap Loyalitas Penggunaan Ponsel Pasca Bayar Esia Surabaya - Nindria Untarini, (Bisnis dan Manajemen, 2010)
This paper is analyzing the influence of marketing mix customer perception that feels and make scoring by post paid customer to ESIA cellular operator in Surabaya. Post paid customer as research object is active customer using their cell phone to become ESIA post paid customer in Surabaya. This research have to be done because understanding customer active is essential for keeping and protect them to switch another cell phone operator. This research purpose to watching carefully the perception about service of marketing mix that bargained by ESIA cellular operator to loyalty of using post paid customer cell phone. The variable in this research taking from Zeithaml and Bitner service marketing theory and Yazid adopt it (1999:21) and the composition7Ps are product, price, place, promotion, participant, physical evidence, and process. Analyze model adapted from Customer Behavior simple model by Assael (1984:11) with using multiple linear regression technique, F test and t test. Base on analyze, can take a resume that marketing mix perception variable (cellular telecommunication service, price, facility ease, promotion, staff servicing, physical evidence, and administration process) post paid ESIA customer feels influenced to using cell phone loyalty at ESIA cellular operator in Surabaya as significantly both of single test and simultaneous test. As a single test, this result can look at each of t test that always have score more than 1,6616. While as simultaneous test, can take a look of F test result is 51,611 that more than score of F table 2,127. From the result of analysis, knows that price of cellular telecommunication that charged to post paid customer have dominant influence to loyalty of cell phone used post paid customer ESIA in Surabaya. While, the variable of facility ease have very little influenced. Base on analyze, can take a resume that marketing mix perception variable (cellular telecommunication service, price, facility ease, promotion, staff servicing, physical evidence, and administration process) post paid ESIA customer feels influenced to using cell phone loyalty at ESIA cellular operator in Surabaya as significantly both of single test and simultaneous test. As a single test, this result can look at each of t test that always have score more than 1,6616. While as simultaneous test, can take a look of F test result is 51,611 that more than score of F table 2,127. From the result of analysis, knows that price of cellular telecommunication that charged to post paid customer have dominant influence to loyalty of cell phone used post paid customer ESIA in Surabaya. While, the variable of facility ease have very little influenced.